Removal of Radioactive Iodine Using Silver/Iron Oxide Composite Nanoadsorbents - Mah Rukh Zia; Muhammad Asim Raza; Sang Hyun Park; Naseem Irfan; Rizwan Ahmed; Jung Eun Park; Jongho Jeon; Sajid Mushtaq (Nanomaterials, 2021)
Efficient and cost-effective removal of radioactive iodine (radioiodine) from radioactive contaminated water has become a crucial task, following nuclear power plant disasters. Several materials for removing radioiodine have been reported in the literature. However, most of these materials exhibit some limitations, such as high production cost, slow adsorption kinetics, and poor adsorption capacity. Herein, we present silver/iron oxide nanocomposites (Ag/Fe3O4) for the efficient and specific removal of iodine anions from contaminated water. The Ag/Fe3O4 were synthesized using a modified method and characterized via scanning electron microscopy, transmission electron microscopy, and X-ray diffraction analyses. This adsorbent showed a high adsorption capacity for iodine anions (847 mg/g of the adsorbent) in pure water. Next, Ag/Fe3O4 was applied to the removal of radioiodine, and high removal efficiencies were observed in water. In addition, its desalination capacity was retained in the presence of competitive ions and varied pH. After the adsorption process, Ag/Fe3O4 was easily removed from the water by applying an external magnetic field. Moreover, the same operation can be repeated several times without a significant decrease in the performance of Ag/Fe3O4. Therefore, it is expected that the findings presented in this study will offer a new method for desalinating radioiodine in various aqueous media.